DEVELOPMENT OF NANOPARTICLES VACCINE HBSAG USING (PHYLANTHUS NIRURI L.) EXTRACT AS ADJUVANT - Sapra, Amriani
Hepatitis B prevalence had been increase every years because it's infect baby and adults. After infection, infected people become carrier for hepatitis B therefore need the development of potent and safe antigen-delivery systems. Immunogenicity of an antigen elicits low immune responses that can be modulated by the usage of adjuvant. HBsAg nanoparticles vaccine encapsulating Phyllanthus niruri L. as adjuvant was developed for optimum effects. Phyllanthus niruri L. as immuno stymulator will be tested and compare it's activity as adjuvant for HBsAg. Nanoparticles were prepared by ionotropic gelation method using chitosan polymer with sodium tripolyphosphate as a cross linker. Ten gg HBsAg was loaded into the particles and doses of P. niruri extract used were 150, 250 and 350 gg, respectively. Two types of nanoparticles were produced in which HBsAg alone or combination of HBsAg-P. niruri was loaded into nanoparticles. Particle size and polydispersity index of the particles were characterized. Additionally, entrapment efficiency of HBsAg and P. niruri extract was determined using silver staining on SDS-PAGE and quercetin marker by UV spectrophotometry, respectively. Immune response effect of HBsAg nanoparticles alone or in combination HBsAg-PN were tested in vitro using dendritic cells by flow cytometry. Parameter of the test was expression co-stymulatory moleculs CD86. The size of HBsAg loaded nanoparticles(H-NP) was 179 nm while PN loaded nanoparticles (P-NP) is having size of around 295-463 nm, when HBsAg along with PN were encapsulated, it has around 230-270 nm size. Results showed optimum entrapment efficiency. Entrapment efficiency of HBsAg in H-NP was 81% while that in the combination of HBsAg-PN loaded nanoparticles (HPN-NP) was more than 97%. Furthermore, entrapment efficiency of PN in PN-NP was also more than 81%,while that in the HPN-NP was in a range 63-70%. In vitro testing showed maturation of dendritic cells but as adjuvant not significant (p<0,05) compare with HBsAg nanoparticle.